DETERMINING AVERAGE SHOCK ABSORBING COEFFICIENT OF THE HYDRAULIC SHOCK ABSORBER OF THE REDUCTION GEAR OF A WINDING MACHINE IN A MINE - Răzvan Bogdan ITU; Vlad Alexandru FLOREA (Fiabilitate şi Durabilitate)
The principal reduction gear of winding machines is mounted on springs, and in order to damp the oscillations produced by the torque generated by the principal electric motor, the reduction gear is fitted with a shock absorber as well. The choice of the characteristics of elasticity and of damping, is an especially important issue. The paper presents determining of the average coefficient of the hydraulic shock absorber from the reduction gear of a mining winding machine.